Analysing the Relationship between Oil Prices and Islamic Stock Markets1. Issue 4 (25th September 2017) - Arshad, Shaista
Abstract : This study is novel in measuring the volatility and efficiency of Islamic stock markets of top oil‐importing countries. Daily prices of six Islamic stock markets are analysed for volatility using EGARCH and efficiency using Multifractal Detrended Fluctuation Analysis, over three different economic regimes. The results indicate a concurrent movement of oil price volatility and Islamic stock market volatility, as Islamic stock markets are heavily reliant on the real economy, which faces the effects of oil price changes. Emerging markets faced higher volatility and lower efficiency than developed counterparts, owing to fast‐paced economic and infrastructural growth, affecting the real sector of the economy.